ACTIVE TRANSTENSION INSIDE CENTRAL ALBORZ: A NEW INSIGHT INTO NORTHERN IRAN-SOUTHERN CASPIAN GEODYNAMICS - Ritz J.F.; Nazari H.; Vernant P.; Ghassemi A.; Salamati R.; Shafei A.; Solaymani S. (My University, 2006)
The tectonic activity in the Alborz mountain range, northern Iran, is due both to the northward convergence of central Iran toward Eurasia, and to the northwestward motion of the South Caspian Basin with respect to Eurasia inducing a left-lateral wrenching along this range. These two mechanisms give rise to a NNE-SSW transpressional regime, which is believed to have affected the entire range for the last 5 ± 2 m.y. In this paper, we show that the internal domain of central Alborz is not affected by a transpressional regime but by an active transtension with a WNW-ESE extensional axis. We show that this transtension is young (middle Pleistocene). It postdates an earlier N-S compression and may have been initiated when the South Caspian Basin started moving. Consequently, our results suggest that the South Caspian Basin motion may have taken place more recently than previously proposed. © 2006 Geological Society of America.
Keywords: ACTIVE TECTONICS; CENTRAL ALBORZ; IRAN; SOUTH CASPIAN BASIN; TRANSTENSION; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен